Impact of Age and Farming Experience on Sugarcane Productivity in the Visayas, Philippines - Oñal, Jr., Paulino A; Samillano, Nena P.; Andrade, Francis E.; Oñal, Paulino Miguel M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Knowledge, experience, and collaboration work hand in hand with one another to improve productivity. The global demographic trends highlight an inversion of the farming-community age pyramid, with those age 65 years and over constituting the fastest growing sub-group of the farming population. The study aims to determine the relationship between the farmers experience and age relative to the production of sugarcane crop in the Philippines. Descriptive method of research was employed in the study. The respondents were the 320 sugarcane farmers that were randomly identified at the seven locations in the Visayas area of the Philippines. An instrument used was the validated survey questionnaire used by Oñal (2021). The result show that there a significant difference in the production of sugarcane among seven location in the Visayas, Philippines. Significant differences among the years of experience and farmers age had an effect on the production. Those who are in farming between 11-12 years and aging 36-50 years old have a high production of >65 TC/ha (alpha=0.01) least experience and young farmers. Furthermore, the farmers experience and their age level are moderately correlated (alpha=0.01). Government and other people organization should provide more scholarship or trainings to include private colleges or universities offering courses in agriculture. Tech-voc courses or trainings offered by TESDA be made available to everyone especially the out of school youth.